Acute ischemic preconditioning does not influence high-intensity intermittent exercise performance - Marocolo, Isabela Coelho (PeerJ, 2017)
This study evaluated the acute effect of ischemic preconditioning (IPC) on a high-intensity intermittent exercise performance and physiological indicators in amateur soccer players. Thirteen players (21.5 ± 2 yrs) attended three trials separated by 3–5 days in a counterbalanced randomized cross-over design: IPC (4 × 5-min occlusion 220 mmHg/reperfusion 0 mmHg) in each thigh; SHAM (similar to the IPC protocol but “occlusion” at 20 mmHg) and control (seated during the same time of IPC). After 6-min of each trial (IPC, SHAM or control), the players performed the YoYo Intermittent Endurance Test level 2 (YoYoIE2). The distance covered in the YoYoIE2 (IPC 867 ± 205 m; SHAM 873 ± 212 m; control 921 ± 206 m) was not different among trials (p = 0.10), furthermore, lactate concentration and rate of perceived exertion did not differ (P > 0.05) among protocols. There were also no significant differences in either mean heart rate (HR) or peak HR (p > 0.05) for both IPC and SHAM compared to control. Therefore, we conclude that acute IPC does not influence high-intensity intermittent exercise performance in amateur soccer players and that rate of perceived exertion, heart rate and lactate do not differ between the intervention IPC, SHAM and control.